17β estradiol activates autophagy and attenuates homocysteine mediated inflammation in endothelial cells through PI3K AKT MTOR signaling - Tong Yu; Dandan Zhang; Yi Yang; Yu Jiang; Jia Wang; Jing Li; Yannan Zhang; Rong Xie; Xiuqin Hong (Scientific Reports)
Abstract The accumulation of plasma Hcy has been linked to vascular inflammation, which can result in vascular dysfunction. Autophagy has been the subject of extensive research in the context of hypertension-related vascular inflammation injury. As demonstrated in a preceding study, the protective effect of estradiol against vascular injury is attributable to its impact on autophagy. The present study has been designed to elucidate the epidemiological relationships between estrogen, homocysteine (Hcy), high-sensitivity C-reactive protein (hs-CRP), and their synergistic effects on the development of hypertension at the population level. In addition, the study will mechanistically investigate how estrogen-mediated autophagy counteracts Hcy-induced inflammatory injury in human umbilical vein endothelial cells through experimental validation. A case-control study was conducted on 559 female patients at Hunan Provincial People’s Hospital, who were divided into hypertensive and normotensive groups. The investigation revealed that the age, Hcy and Hs-CRP concentration of the hypertensive group exceeded those of the normotensive group (P < 0.001). Conversely, the estrogen level exhibited the opposite trend (P < 0.001). The logistic regression analysis indicated that plasma estrogen levels are a beneficial factor in relation to hypertension. Conversely, plasma Hcy and Hs-CRP levels have been shown to be detrimental, and there is an interaction between the two. In the preliminary experiment, the presence of 17β-estradiol (E2) was observed to stimulate the proliferation of Hcy-treated umbilical vein endothelial cells, whilst concomitantly exerting an inhibitory effect on inflammation. The present study demonstrated that Hcy inhibited autophagy in cultured human umbilical vein endothelial cells (HUVECs), while E2β reversed this inhibition. In conclusion, the present study demonstrated that 17β-estradiol attenuates homocysteine-induced inflammatory injury in HUVECs through the activation of autophagy via the PI3K/Akt/mTOR signalling axis.